Analysis of the Effects and Causes of Driver Horn Use on the Acoustic Environment at Urban Intersections in Taiwan - Masayuki Takada; Shoki Tsunekawa; Kazuma Hashimoto; Tamaki Inada; Ki-Hong Kim; Yoshinao Oeda; Katsuya Yamauchi; Shin-ichiro Iwamiya (Applied Sciences, 2022)
Car horns were originally installed in vehicles for safety. However, many urban areas in several countries face noise problems related to the use of car and motorbike horns. To propose measures to suppress the use of horns, relationships between horn use and factors including driver awareness and behavior, traffic environment, and the transportation system should be investigated. The present study therefore conducted surveys to grasp the current circumstances of horn use and traffic at urban intersections in Taiwan. The relationship between horn use and the traffic volume of standard-sized vehicles was found. According to an analysis of horn use during traffic signal cycles, in many cases, horns were honked after entering intersections to turn left. In particular, horns were honked when the driver waited more than 4 s for the car in front to start moving after the green light allowing left turns was turned on. An analysis of noise levels at intersections showed that the maximum noise level value (LAmax) could be reduced if vehicle horns were not used. Multiple regression analysis also indicated that LAmax values increased with the frequency of horn use. The equivalent continuous A-weighted sound pressure level (LAeq,10min) did not change with driver horn use, and increased with the traffic volume of motorcycles.